2012
DOI: 10.2147/opth.s30611
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ocular hypotensive effect and safety 12 months after changing from an unfixed combination to a latanoprost 0.005% + timolol maleate 0.5% fixed combination

Abstract: BackgroundLatanoprost 0.005% + timolol maleate 0.5% combined eyedrops were recently made available in Japan. We prospectively investigated the intraocular pressure (IOP)-lowering effect, visual preservation effect, and adverse reactions of a one-year administration of this fixed combination.MethodsThe subjects included 162 eyes from 162 patients diagnosed with either primary open-angle glaucoma or ocular hypertension and using an unfixed combination of latanoprost 0.005% and timolol maleate 0.5%. The unfixed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
2
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 8 publications
2
15
2
2
Order By: Relevance
“…Compared to our previous studies of other prostaglandin/timolol fixed combinations, less adverse reactions were observed in this study (6.8% in latanoprost/timolol, 11 16.3% in travoprost/timolol, 13 5.9% in this TTFC study). The difference in the incidence of adverse reactions may be partly explained by the shorter observation period of the present study compared with the previous studies (8 weeks vs 12 months 11 and 6 months 13 ), and by use of multiple medications in the study on the travoprost/timolol fixed combination 13 (the prostaglandin analog was either latanoprost, travoprost, tafluprost, or isopropyl unoprostone and the β-blocker was either timolol, carteolol, levobunolol, or nipradilol). In this study, we found that the pulse rate and systolic blood pressure did not change after switching, but the diastolic blood pressure decreased significantly.…”
Section: Discussioncontrasting
confidence: 89%
“…Compared to our previous studies of other prostaglandin/timolol fixed combinations, less adverse reactions were observed in this study (6.8% in latanoprost/timolol, 11 16.3% in travoprost/timolol, 13 5.9% in this TTFC study). The difference in the incidence of adverse reactions may be partly explained by the shorter observation period of the present study compared with the previous studies (8 weeks vs 12 months 11 and 6 months 13 ), and by use of multiple medications in the study on the travoprost/timolol fixed combination 13 (the prostaglandin analog was either latanoprost, travoprost, tafluprost, or isopropyl unoprostone and the β-blocker was either timolol, carteolol, levobunolol, or nipradilol). In this study, we found that the pulse rate and systolic blood pressure did not change after switching, but the diastolic blood pressure decreased significantly.…”
Section: Discussioncontrasting
confidence: 89%
“…Moreover, in a meta-analysis comparing the effectiveness of concomitantly used prostaglandin analog and timolol maleate eyedrops with that of prostaglandin analog–timolol maleate fixed-combination eyedrops, the fixed-combination eyedrops were less effective in reducing IOP than the concomitantly used eyedrops 8. The proportion of cases in which the eyedrops were changed because of insufficient IOP-decreasing efficacy increased by 20.4% in the present study when compared to that 1 year after the change (12.3%) 2. These data suggest that the IOP-decreasing effect of the β-blockers in fixed-combination eyedrops weakens after long-term administration of these drops.…”
Section: Discussioncontrasting
confidence: 53%
“…In a previous report, the IOP-decreasing efficiency, visual field-preservation effect, and safety of changing a latanoprost and timolol maleate eyedrop regimen to the latanoprost–timolol maleate fixed-combination eyedrop regimen were investigated over a 1-year period 2. No significant differences were found in the IOP before the change and at 3, 6, 9, and 12 months after the change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…zu führen. Einige jüngere Studien haben die mögliche Auswirkung einer Umstellung von 2 separaten Präpara-ten Latanoprost und Timolol auf die fixe Kombination aus Latanoprost/Timolol untersucht und konnten keine statistisch eindeutige Änderung beim IOD nachweisen[15,16]. Beide zitierten Studien wiesen aber im Beobachtungszeitraum eine höhere Rate an Therapiebeendigungen wegen eines insuffizienten IODs auf (8% innerhalb von 3 Monaten und 20% innerhalb von 12 Monaten).Fixe Kombinationspräparate aus Timolol und Prostaglandinanaloga zeigen einen additiv drucksenkenden Effekt im Vergleich zu den jeweiligen Monotherapien.…”
unclassified